Diversidade e interação de insetos galhadores na Caatinga - Marinho, Rafael Aguiar (2022)
Galls are alterations in the plant tissue of host plants triggered mainly by insects. In this thesis, I carried out a survey of the occurrence of galls in six vegetation remnants of caatinga s.s. and tested hypotheses to explain the variation in gall richness in conserved and degraded environments. The thesis has two main chapters. In the first one, the results of a survey and characterization of entomogenous galls in remnants of caatinga present in the Sertaneja Setentrional Depression are presented. Two sites were selected in the state of Paraíba, two in Rio Grande do Norte and two in Ceará. A sampling of galls and their host plants was conducted during the rainy season, from February to June 2019, and from February to May 2021. 41 morphotypes of galls present in 24 species of host plants were identified. The plants belong to 12 families of Angiosperms and Fabaceae harbored 29.2% (n=12) of the total identified gall morphotypes. Most morphotypes are glabrous (75.6%), while only 24.4% exhibited trichomes. Leaves (61%) and stems (25%) were the most attacked organs. Most galls were induced by insects of the Cecidomyiidae family. The associated fauna comprised successors, caecidophages, tenants and parasitoids. The first, found in four morphotypes of galls, are represented by spiders and four orders of insects: Hemiptera, Coleoptera, Lepidoptera and Hymenoptera (Formicidae). The tenants were represented by Tanaostigmoides Ashmead, 1896 (Tanaostigmatidae). The parasitoids, found in 18 morphotypes of galls (43.9%), belong to six families of Hymenoptera. All gall records are new references for the studied states in the Northern Sertaneja Depression. The second chapter presents the richness and abundance of plants and their relationship with the richness and abundance of galling insects. Ecological models for plant and galls richness were analyzed using the Poisson error distribution and for plant and galling abundance using the negative binomial distribution. In the selection of sampling areas, we used the HumanFootPrint (HFP), an index that measures the human impact on the non-Antarctic surface of the Earth. We selected a total of six areas, three considered to have low impact (HFP < 5) and three to have high human impact (HFP > 19). In low impacted areas, the richness of plants and galls was higher than in the most impacted. The composition of plant and gall communities was significantly different between environments. However, in the most conserved environments the composition of the plant community directly influenced the composition of galling insect community.